Online data collection strategies in qualitative nursing research - Menezes , Layla de Cassia Bezerra Bagata; Brasileiro , Tânia Suely Azevedo (Seven Editora, 2024)
The rapid evolution of technology and the widespread dissemination of the Internet have provided a significant transformation in the field of qualitative research in nursing. This chapter seeks to briefly discuss data collection strategies in qualitative research. To this end, this literature review is divided into two moments: initially, it focuses on the historical evolution of these data collection instruments, since the emergence of writing and, subsequently, it synthesizes the online data collection strategies that are being used in qualitative research in nursing, based on an integrative review in the Virtual Health Library. The search in the database resulted in 150 findings, to which the inclusion and exclusion criteria were applied, leaving 6 articles for inclusion in the study, submitted to a careful analysis. The results of this study are presented in four discussion topics, namely: Cuneiform writing and data recording: a brief history; Contemporary applications of online data collection in qualitative research in nursing; Benefits and limitations of online data collection; Trends and future perspectives in online research. Online data collection strategies are highly viable in qualitative research, especially because they are far-reaching, low-cost, and easily accessible. DOI: https://doi.org/10.56238/sevened2023.007-018